2014
DOI: 10.1155/2014/968487
|View full text |Cite
|
Sign up to set email alerts
|

A Broad-Spectrum Antimicrobial Activity ofBacillus subtilisRLID 12.1

Abstract: In the present study, an attempt was made to biochemically characterize the antimicrobial substance from the soil isolate designated as RLID 12.1 and explore its potential applications in biocontrol of drug-resistant pathogens. The antimicrobial potential of the wild-type isolate belonging to the genus Bacillus was determined by the cut-well agar assay. The production of antimicrobial compound was recorded maximum at late exponential growth phase. The ultrafiltered concentrate was insensitive to organic solven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 25 publications
6
40
0
Order By: Relevance
“…Shelburne et al [23] reported that subtilosin A (3,399.7 Da) from B. subtilis displayed an MIC of > 200 mg/L against S. epidermidis ATCC 12228 and > 100 mg/L against E. coli. In another study, partially purified bacteriocin from soil isolate B. subtilis RLID 12.1 inhibited the growth of S. epi dermidis at > 200 µg/mL and did not exhibit any activity against E. coli [24]. The bacteriocin in our study displayed antimicrobial activity against a broad spectrum of grampositive and gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 50%
“…Shelburne et al [23] reported that subtilosin A (3,399.7 Da) from B. subtilis displayed an MIC of > 200 mg/L against S. epidermidis ATCC 12228 and > 100 mg/L against E. coli. In another study, partially purified bacteriocin from soil isolate B. subtilis RLID 12.1 inhibited the growth of S. epi dermidis at > 200 µg/mL and did not exhibit any activity against E. coli [24]. The bacteriocin in our study displayed antimicrobial activity against a broad spectrum of grampositive and gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 50%
“…It has been also reported that Bacillus subtilis [28] and E. faecium [29] inhibited the growth of E. coli. Furthermore, the ultrafiltered concentrate of the cell-free culture of B. subtilis showed inhibitory effects against E. coli [30]. In both protocols, the culture broth was taken to test antibacterial activity.…”
Section: Resultsmentioning
confidence: 99%
“…The isolate was grown in MRS broth (HiMedia, M369), without heavy metals at 37°C for 24 h. After incubation, the optical density of the broth culture was adjusted to OD600 = 0.1 using a light spectrophotometer (JENWAY, 7305). A loopful of the broth culture was then aseptically streaked onto MRS agar (HiMedia, M641) supplemented with different heavy metals (Hg, Cr, Cd, and Pb), respectively, at different concentration (10,20,30,40, and 50 ppm). The plates were then incubated at 37°C for 48 h. Single colonies or trace of growth was ignored.…”
Section: Determination Of Minimum Inhibitory Concentration (Mic)mentioning
confidence: 99%
“…In the present investigation, the antibacterial activity of 25 Bacillus isolates against wide range of Gram-positive and Gram-negative bacteria were demonstrated. These isolates were identified based on their morphological, physical, and biochemical characteristics using Bergey"s manual and other scientific literature (Arbsuwan et al, 2014;Arumugam et al, 2017;Ramachandran et al, 2014;Malanicheva et al, 2012). It has been also observed that highest antibacterial activity was demonstrated against S. aureus and S. epidermis than E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…subtilis, B. lichenoformis, B. coagulans, B. us megaterium, B. polymyxa, and Brevibacillus brevis. (Arbsuwan et al, 2014;Arumugam et al, 2017;Jianmei et al, 2015;Ramachandran et al, 2014;Malanicheva et al, 2012;Sumi et al, 2015).…”
Section: Identification Of Isolatesmentioning
confidence: 99%